A case for integrated development: pathways to improve child well-being. Issue 1 (2nd January 2017) - Rutherford, Diana Duff; Bachay, Jessica
ABSTRACT: Economic strengthening interventions may increase income, assets, and food security. Donors and implementers see the potential for improvements in child well-being. This article presents lessons learnt from the implementation of two economic strengthening interventions. It finds missed opportunities with regard to child nutrition, and recommends: (1) integrating economic strengthening interventions with complementary development activities; (2) deep formative assessment to inform programme design; and (3) the use of community-based feedback loops. Development practitioners, funders, policymakers, and researchers must take every opportunity to improve the lives of children as young as possible to build healthy families, communities, and nations.